Need Analysis on English as Professional Skills for Students of Islamic Elementary School Teacher Education: English - Zakaria Bintang Pamungkas Pamungkas (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
This study seeks to analyze the professional English skill requirements of third-semester students in the Islamic Elementary Teacher Education program at the Islamic Institute of Riyadlotul Mujahidin Ngabar Ponorogo and to design an effective English learning framework that is suitable for their professional preparation. The research specifically addresses the linguistic competencies needed by future Islamic elementary teachers in their workplace contexts. A qualitative descriptive design was applied, involving questionnaires, interviews, and document reviews to collect data from students, lecturers, and relevant stakeholders. The results demonstrate that English proficiency plays a vital role in preparing students to teach English for young learners (TEYL). Students are required to enhance their communicative abilities, particularly in classroom interaction, academic writing, and accessing English-based TEYL resources. Furthermore, the study reveals a noticeable gap between the existing curriculum and the actual linguistic demands in educational practice. The learning situation analysis emphasizes the importance of developing all English language skills for professional readiness. Therefore, the proposed English learning model integrates mastery of language components with communicative learning strategies through authentic audio-visual materials. Activities such as listening, vocabulary enrichment, dialogue practice, peer learning, and role play are essential to encourage active use of English and foster students’ teaching competence.